Media Sosial: Wadah Baru Evangelisasi - Bartolomeus Sihite (Jurnal Magistra, 2024)
Nowadays, we have moved into the second oral era, enlivened by television and information technology. So the 'virtual world' grew which was supported by new tools with all the charming facilities. The changing reality of the world around us is a context that must be taken into account if we want to carry out faith preaching activities. The main problem of preaching in this era is not "what communication tools we should use" but "what kind of communication methods we need to use so that the message of faith is relevant to people living in the digital age." The Church recommends that pastors and people see positive opportunities from the media, while increasing awareness of the negative impacts of the media. It is not enough to simply use the media to spread authentic Christian messages and Church teachings. It is also necessary to integrate the Gospel message in the new culture created by modern communications. If the language of preaching which covers the entire appearance of the Church, its behavior, structure and attitudes is not updated, people today will not grasp the message conveyed by the Church. We must look for ways that can touch the sensibilities of modern society.